Principals in Succession
X, 174 p.
Keywords: Contributors to this volume examine structures and processes that school boards have in place directly relating to the process of principal or vice-principal succession. As well, they consider the effect that these structures and processes have upon staff and administrators themselves. These contributors investigate policies, procedures and practices that school boards employ in terms of leadership succession, and explore implications of these constructs for the sustainability of school improvement. This volume presents an overview of the process of principal or vice-principal succession, descriptions of school district practices surrounding this process and discussions regarding how succession procedures affect individuals and groups of individuals. This volume also highlights those board policies that incorporate practices used to develop models that support and allow administrators to succeed. It articulates how school leaders and staff members deal with change and improvement efforts in successive schools, as well as how board policies and practices support principals and vice-principals at any stage in the succession process. This volume is useful as a reference guide relating to transfer and rotation procedures in school systems across the nation.